SANITASI PONOOK PESANTREN MATHLABUL ULUM 01 OESA JAMBU KECAMATAN LENTENG KABUPATEN SUMENEP TAHUN 2014 - Ulfatun Nushush; Suparlan .; Hadi Suryono (Poltekkes Kemenkes Surabaya, 2014)
Basicsanitary condition in boarding schools is an effort to control physical environmental factorswhich may otherwise result in negative impacts on the health of the occupants and local people aroundthe boarding schools. One boarding school named